Morphological study of the reproductive system and ovarian growth of the univoltine bamboo borer, Omphisa fuscidentalis (Hampson, 1896) (Lepidoptera: Crambidae). Issue 3 (3rd July 2019) - Kunluang, Sirin; Yasanga, Thippawan; Suang, Suphawan; Manaboon, Manaporn
ABSTRACT: The female reproductive system and protein deposition in the ovaries during development have never been examined in the bamboo borer Omphisa fuscidentalis Hampson. The aim of this study was thus to study the morphology of the female reproductive system of each stage of development. The female reproductive system of the borer consists of a pair of ovary, oviduct and accessory glands. Each ovary is composed of four polytrophic ovarioles that connect to lateral oviducts, fused with a common oviduct. The size of the ovary in diapausing larvae for 9 months was determined. The length and width of the ovaries were the smallest in September larvae (0.343 ± 0.03 and 0.071 ± 0.01 mm, respectively). The ovaries were the largest during ovarian development in May (0.752 ± 0.08 mm long and 0.084 ± 0.01 wide). Additionally, ovarian size was significantly larger in adults than in pupae. The ovarian protein concentration of larvae in May was 0.59 ± 0.06 mg/ml and increased to 16.61 ± 7.5 and 37.42 ± 5.5 mg/ml in pupae (June) and adults (July), respectively. The results showed ovarian development in all life stages of this holometabolous insect, which has a longer life cycle than other lepidopterans. Abbreviation: TEM: transmission electron microscope